Design and analysis of single layer quantum dot-cellular automata based 1- bit comparators - Ziyad A. Altarawneh; Mutaz A.B Al-Tarawneh (Universitas Ahmad Dahlan, 2022)
Quantum dot-cellular automata (QCA) technology has recently emerged as a potential candidate for the design of nanometer-scale computational circuits. In digital logic circuits, the comparator is the basic building block for comparing two binary values. This paper presents and implements two 1-bit QCA-based comparator designs. The proposed QCA implementations are compact, require only a single layer and are less complex compared to recently reported designs. The QCADesigner tool has been used to confirm the functional validity of the proposed QCA structures. The simulation results of the proposed comparators have shown considerable improvements compared to their existing counterparts in terms of the number of QCA cells and occupational area requirements in addition to cost and efficient complexity values. Furthermore, all of the proposed structures are dissipating extremely low energy values. Thus, the proposed QCA-based comparators can be viewed as viable options for low power digital applications.